Rancang Bangun Sistem Informasi Warga Berbasis Mobile pada RW 006 Kelurahan Cipinang Jatinegara Jakarta Timur - Mulyana, Dadang Iskandar; Hudzaifah, Salim Maula; Al Ammar, Muhammad Farros; Siregar, Ikhsan Abror (Jurnal Pengabdian Nasional (JPN) Indonesia, 2024)
Rukun Tetangga/Community Association, hereinafter abbreviated as RT/RW, is an institution formed through RT/RW deliberations which has an important role in maintaining and preserving community values based on cooperation and kinship; expediting the implementation of government duties in the field of rural or urban and community development, as well as empowering all government organizations and the business world to improve community welfare. Therefore, RT/RW must provide good services to their citizens to create a conducive society. People need services at any time, but these services can only be provided to residents in the afternoon or on holidays because RT/RW administrators have personal interests. Currently, the quality of public services provided by government institutions is still not optimal, services to the community are not running optimally. This problem can be overcome by building a mobile-based citizen information system that is capable of being a communication medium between residents and RT/RW administrators. Through the use of mobile technology, citizen information systems enable citizens to quickly access information related to community activities, important announcements, and public services available around them. This application also makes it easier for residents to report problems or community needs directly through an integrated reporting feature. Thus, it is hoped that the adoption of this technology can have a positive impact in improving the quality of life and strengthening the social ties of local communities. This application aims to make it easier to get information about activities/events or other necessary information, as well as make it easier to make reports or complaints in the form of a mobile application.